2017
DOI: 10.1038/s41598-017-06058-6
|View full text |Cite
|
Sign up to set email alerts
|

Physiological stress-induced corticosterone increases heme uptake via KLF4-HCP1 signaling pathway in hippocampus neurons

Abstract: Iron overload has attracted much attention because of its adverse effect in increasing the risk of developing several neurodegenerative disorders. Under various pathologic conditions, a lot of heme are released. The aggregation of heme is more neurotoxic than that of iron released from the heme breakdown. Our previous studies demonstrated that psychological stress (PS) is a risk factor of cerebral iron metabolism disorders, thus causing iron accumulation in rat brains. In the present study, we found PS could i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…These family members are tied to various biological roles, such as differentiation of myelinating oligodendrocytes, 10 remyelination, 12 axonal regeneration, 11 and stress-induced iron uptake. 20 Previous studies have also identified increased accessibility of KLF transcription factors in oligodendroglia in the EAE mouse model of MS. 21 The detection of 19 KLF/SP transcription factors in MS oligodendrocytes could imply their cross-regulation of gene expression to counteract the hypomyelination and axonal impairment under iron-induced stress. The stress in oligodendrocytes might be exacerbated by the downregulation of SLC7A11 , a cystine/glutamate antiporter essential for glutathione (GSH) production.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These family members are tied to various biological roles, such as differentiation of myelinating oligodendrocytes, 10 remyelination, 12 axonal regeneration, 11 and stress-induced iron uptake. 20 Previous studies have also identified increased accessibility of KLF transcription factors in oligodendroglia in the EAE mouse model of MS. 21 The detection of 19 KLF/SP transcription factors in MS oligodendrocytes could imply their cross-regulation of gene expression to counteract the hypomyelination and axonal impairment under iron-induced stress. The stress in oligodendrocytes might be exacerbated by the downregulation of SLC7A11 , a cystine/glutamate antiporter essential for glutathione (GSH) production.…”
Section: Discussionmentioning
confidence: 96%
“…Oligodendrocytic-specific enrichment of transcription factor binding motifs implicated the activation of the KLF/SP family. KLF/SPs are known to function in a wide variety of biological processes 18 , where SP2 is involved in differentiation of myelinating oligodendrocytes 7 , KLF9 regulates regeneration of myelin 9 , and KLF4 is involved in axonal regeneration 8 and stress-induced iron uptake 19 . That may reflect the functional heterogeneity of MS oligodendrocytes previously described in snRNA-seq of WM lesions 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Reports depicted a high expression of KLF4 in neural stem cells and different parts of the brain, like the hypothalamus, hippocampus, and cerebral cortex [ 11 , 13 , 18 , 54 , 55 ]. Many studies demonstrated KLF4 regulatory role in neuronal apoptosis, neuroinflammation, and nerve regeneration [ 17 , 18 , 55 , 56 ]. KLF4 is involved in the regulation of neuroinflammation in AD.…”
Section: Overview Of Klf4mentioning
confidence: 99%
“…A recent study demonstrated that physiological stress caused activation of the KLF 4 -HCP1 signaling pathway and increased heme uptake ( Li H. et al, 2017 ). Heme accounts for 95% of the functional iron in the human body.…”
Section: Role Of Klf 4 In Admentioning
confidence: 99%
“…This has a relief effect on AD. Physiological stress induces glucocorticoid level rise, glucocorticoid increases heme carrier protein 1 (HCP1) expression via KLF 4 , and then HCP1 promotes heme uptake ( Li H. et al, 2017 ). Glucocorticoid and KLF 4 regulate anti-inflammatory genes together, and cells with low glucocorticoid content cannot fully induce KLF 4 expression ( Sevilla et al, 2015 ).…”
Section: Role Of Klf 4 In Admentioning
confidence: 99%